Individualized Radiation Dose Escalation Based on the Decrease in Tumor FDG Uptake and Normal Tissue Constraints Improve Survival in Patients With Esophageal Carcinoma. (February 2017) - Ma, Jinbo; Wang, Zhaoyang; Wang, Chengde; Chen, Ercheng; Dong, Yaozong; Song, Yipeng; Wang, Wei; You, Dong; Jiang, Wei; Zang, Rukun
Background: To determine whether individualized radiation dose escalation after planned chemoradiation based on the decrease in tumor and normal tissue constraints can improve survival in patients with esophageal carcinoma. Methods: From August 2005 to December 2010, 112 patients with squamous esophageal carcinoma were treated with radical concurrent chemoradiation. Patients received positron emission tomography-computer tomography scan twice, before radiation and after radiation dose of 50.4 Gy. All patients were noncomplete metabolic response groups according to the Response Evaluation Criteria in solid tumors. Only 52 patients with noncomplete metabolic response received individualized dose escalation based on tumor and normal tissue constraints. Survival and treatment failure were observed and analyzed using SPSS (13.0). Results: The rate of complete metabolic response for patients with noncomplete metabolic response after dose escalation reached 17.3% (9 of 52). The 2-year overall survival rates for patients with noncomplete metabolic response in the conventional and dose-escalation groups were 20.5% and 42.8%, respectively( P = .001). The 2-year local control rates for patients were 35.7% and 76.2%, respectively ( P = .002). When patients were classified into partial metabolic response and no metabolic response, 2-year overall survival rates for patients with partial metabolic response were significantly different in conventional and dose-escalation groups (33.8% vs 78.4%; P = .000). The 2-year overall survival rates for patients with no metabolic response in two groups (8.6% vs 15.1%) did not significantly differ ( P = .917). Conclusion: Individualized radiation dose escalation has the potential to improve survival in patients with esophageal carcinoma according to increased rate of complete metabolic response. However, further trials are needed to confirm this and to identify patients who may benefit from dose escalation.